The Post-Processing of Additive Manufactured Polymeric and Metallic Parts - Daniyar Syrlybayev; Aidana Seisekulova; Didier Talamona; Asma Perveen (Journal of Manufacturing and Materials Processing, 2022)
The traditional manufacturing industry has been revolutionized with the introduction of additive manufacturing which is based on layer-by-layer manufacturing. Due to these tool-free techniques, complex shape manufacturing becomes much more convenient in comparison to traditional machining. However, additive manufacturing comes with its inherent process characteristics of high surface roughness, which in turn effect fatigue strength as well as residual stresses. Therefore, in this paper, common post-processing techniques for additive manufactured (AM) parts were examined. The main objective was to analyze the finishing processes in terms of their ability to finish complicated surfaces and their performance were expressed as average surface roughness (Sa and Ra). The techniques were divided according to the materials they applied to and the material removal mechanism. It was found that chemical finishing significantly reduces surface roughness and can be used to finish parts with complicated geometry. Laser finishing, on the other hand, cannot be used to finish intricate internal surfaces. Among the mechanical abrasion methods, abrasive flow finishing shows optimum results in terms of its ability to finish complicated freeform cavities with improved accuracy for both polymer and metal parts. However, it was found that, in general, most mechanical abrasion processes lack the ability to finish complex parts. Moreover, although most of post-processing methods are conducted using single finishing processes, AM parts can be finished with hybrid successive processes to reap the benefits of different post-processing techniques and overcome the limitation of individual process.